FAKTOR YANG MEMENGARUHI CASH HOLDING PADA PERUSAHAAN SEKTOR PROPERTI DAN REAL ESTATE - Varella, Josephine Isabel; Widjaja, Chelsya; Susanto, Liana (Jurnal Paradigma Akuntansi, 2025)
This research purpose is to find out factors that influenced cash holding of property and real estate companies listed on the Indonesia Stock Exchange for the period of 2019-2021. Those factors include firm size, leverage, and capital expenditure. Sample size of this research are 45 companies selected by using a purposive sampling method. The data are analyzed using multiple linear regression technique which were processed by IBM SPSS 25 for Windows and Microsoft Excel 2016. The research results show that firm size, leverage, and capital expenditure influenced cash holding simultaneously. Firm size and capital expenditure show a positive and significant effect on cash holding whilst leverage shows a negative and significant effect on cash holding. The implication of this research is adding insight for management about cash holding.